The Constitutional Responsibility of the President of the Republic of Iraq: Omission in Regulation and Trial Problems : An Analytical Study - Ahmed, Shaho (Journal of Legal Sciences, 2026)
The post of President of the Republic occupies a high sovereign position in the constitutional structure of the federal authorities. The constitutional legislature has paid great attention to the competencies and responsibilities of this post and its importance in critical and sensitive times and circumstances, and has devoted numerous articles and provisions to this end. Although Iraq’s political system is a parliamentary republic, the Constitution did provide for the possibility to hold the President accountable to the Council of Representatives, but it is not fully detailed and is not a ground for his dismissal or relieving him from office. This step can only be taken if the Federal Supreme Court finds the President of the Republic guilty of a specific constitutional violation, such as violating the Constitution, perjury of the constitutional oath, and committing high treason. Due to constitutional and legislative omissions in this domain, and in accordance with the Constitution, the President of the Republic may be convicted only by the adoption of a specific legislation laying down rules on the procedure for bringing charges and on the trial of such accusations before this court. However, no step has been taken to address this legislative deficiency, which has led to the failure of all attempts to constitutionally trail the President. The Federal Supreme Court attempted to bridge this deficiency on its own through its internal regulation. However, this measure is inconsistent with the Constitution, and the attempt was ultimately overturned by a new internal regulation. Therefore, it is crucial to address this deficiency to ensure maintaining balance between the constitutional competencies and duties of the President of the Republic, as well as to avoid allowing him to evade potential trial by the constitutional court.